An Assessment of The Impact of One Day Training Programme on Knowledge and Attitude of Undergraduate Students on Leprosy at G. R Medical College, Gwalior, Madhya Pradesh - Ranjana Tiwari; Dhiraj Kumar Srivastava; Manoj Bansal; Parharam Adhikari; Shraddha Mishra (Medsci Publications, 2013)
Background: Leprosy which is also known as hansen's disease is probably the oldest disease known to mankind. It is imperative for the young medical students who become future physicians to be well aware about the signs and symptoms along with management of leprosy in India. Objectives: The present study was under taken with the objective to assess the knowledge and attitude of medical students towards leprosy and leprosy affected patients. The present study also aims to study the impact of one day training programme on the change of knowledge and attitude towards leprosy and leprosy affected patients. Material & Methods: The study was a cross sectional study. It was a part of a one day training programme oriented for the up gradation of knowledge about the recent advances in the field of leprosy management and also to highlight the salient features of National Leprosy Eradication Programme (NLEP). All the students who reported on that day were given a questionnaire to be filled before the start of the training programme and after the completion of the training programme. Result: It was noted that majority of the study participants were aware about Multi Drug Therapy (MDT) but awareness about the other aspects of leprosy was very low. The majority of the study participants were having a negative attitude towards the leprosy affected persons which changed significantly after the training programme. Conclusion: Such training programme should be regularly organized for the undergraduate student as these may not only increase the knowledge of the undergraduate students but also have a positive change in the attitude of students.